Imprint of intrinsic ocean variability on decadal trends of regional sea level and ocean heat content using synthetic profiles - William Llovel; Nicolas Kolodziejczyk; Sally Close; Thierry Penduff; Jean-Marc Molines; Laurent Terray (Environmental Research Letters, 2022)
The global ocean is warming and has absorbed 90% of the Earth Energy Imbalance over 2010–2018 leading to global mean sea level rise. Both ocean heat content (OHC) and sea level trends show large regional deviations from their global means. Both quantities have been estimated from in-situ observations for years. However, in-situ profile coverage is spatially uneven, leading to uncertainties when assessing both OHC and sea level trends, especially at regional scale. Recently, a new possible driver of regional sea level and OHC trends has been highlighted using eddy-permitting ensemble ocean simulations over multiple decades: non-linear ocean processes produce chaotic fluctuations, which yield random contributions to regional decadal OHC and sea level trends. In-situ measurements capture a combination of the atmospherically-forced response and this intrinsic ocean variability. It is therefore important to understand the imprint of the chaotic ocean variability recorded by the in-situ measurement sampling in order to assess its impact and associated uncertainty on regional budgets. A possible approach to investigate this problem is to use a set of synthetic in-situ -like profiles extracted from an ensemble of forced ocean simulations started from different states and integrated with the same atmospheric forcing. Comparisons between the original ensemble outputs and the remapped, subsampled, in-situ -like profiles elucidate the contribution of chaotic ocean variability to OHC and regional sea level trends. Our results show that intrinsic variability may be large in eddy-active regions in the gridded model outputs, and remains substantial when using the in-situ sampling-based estimates. Using the latter, the same result is also found on large scales, for which atmospheric forcing has been identified as the main driver. Our results suggest accounting for this intrinsic ocean variability when assessing regional OHC and sea level trend budgets on decadal time scales.